Use of fertility preservation services in male reproductive-aged cancer patients - Jessica Selter; Yongmei Huang; S. Zev Williams; Paula C. Brady; Alexander Melamed; Dawn L. Hershman; Jason D. Wright (Elsevier, 2021)
While fertility preservation is a major concern among reproductive age cancer patients, little is known about access and use of fertility preserving services. We examined use of fertility preserving services among men with common solid tumors.A total of 3648 men age 18-40 including 2610 (71.6%) with testicular cancer, 939 (25.7%) with colorectal and 99 (2.7%) with prostate cancer were identified. Fertility preservation services were utilized in 9.3% of men overall including 4.1% who underwent fertility evaluation only and 7.8% who had a fertility preservation procedure. The rate of fertility preservation services rose from 6.6% (95%CI, 3.2-10.0) in 2008 to 12.4% (95%CI, 7.3-17.5) in 2017 (P = 0.04).Use of fertility preservation service was more common in patients with testicular (11.6%, aRR = 3.31; 95% CI 2.22-4.92) and prostate cancer (6.1%, aRR = 3.14; 95% CI 1.28-7.70) compared to those with colon cancer (3.4%). Younger men were more likely to utilize fertility preservation services. 11.5% of men age ≤ 35 years vs. 5.2% of men 36-40 used these services (P < 0.0001). Fertility preservation services were used in 10.8% of those who received chemotherapy (aRR = 1.81; 95% CI, 1.45-2.27) and in 8.1% of those who received radiation (aRR = 1.30 95% CI, 0.98-1.73). Medicaid patients were less likely to receive fertility preservation services than those with commercial insurance (0.7% vs. 10.1%; aRR = 11.58, 95%CI 2.10-63.69). These data indicate that while use of fertility preserving services is increasing, overall use of services is low among reproductive age males with cancer.